Prevention of autosomal dominant retinitis pigmentosa by systemic drug therapy targeting heat shock protein 90 (Hsp90) - FARRAR, JANE; KENNA, PAUL; KIANG, ANNA-SOPHIA; HUMPHRIES, MARIAN; HUMPHRIES, PETER; TAM, LAWRENCE; CAMPBELL, MATTHEW (My University, 2010)
Retinitis pigmentosa (RP) is the most prevalent cause of registered visual handicap among working aged populations of developed countries. Up to 40% of autosomal dominant cases of disease are caused by mutations within the rhodopsin, RDS-peripherin and inosine 5?-monophosphate dehydrogenase type 1 (IMPDH1) genes, at least 30 mutations within which give rise to proteins that cause disease pathology by misfolding and aggregation. Given the genetic complexity of this disease, therapies that simultaneously target multiple mutations are of substantial logistic and economic significance. We show here, in a murine model of autosomal dominant RP (RP10) involving expression of an Arg224Pro mutation within the IMPDH1 gene, that treatment with the low-molecular-weight drug, 17-allylamino-17-demethoxygeldanamycin (17-AAG), an ansamycin antibiotic that binds to heat shock protein Hsp90, activating a heat shock response in mammalian cells, protects photoreceptors against degeneration induced by aggregating mutant IMPDH1 protein, systemic delivery of this low-molecular-weight drug to the retina being facilitated by RNA interference-mediated modulation of the inner-blood retina barrier. 17-AAG has an orphan drug status and is in current clinical use for the treatment of non-ocular diseases. These data show that a single low-molecular-weight drug has the potential to suppress a wide range of mutant proteins causing RP.
PUBLISHED
Keywords: Genetics; Retinitis pigmentosa (RP); Genes & Society